A look at the history of pottery - Batir Baratboyev Mamadjanovich; Sharaboyev Ulug`bek Muhamedovich (Research Parks Publishing LLC, 2020)
This article reveals the history of the origin of art pottery, archeological artifacts found in the territory of Uzbekistan, the creation of the art of pottery, philosophical views on the creative work of ceramics.